PENGARUH PARTISIPASI MASYARAKAT TERHADAP PROSES MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KECAMATAN KAPUAS KABUPATEN SANGGAU - Susanti Susanti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
The research aims at investigating the level of citizen participation in the process of sub-district development planning, analyzing the process of the planning and decision making, and examining the influence of citizen participation on the process of sub-district development planning at Kapuas Sub-district, Sanggau. It employs quantitative, explanatory method. The instruments of the research comprise questionnaires, interview, and documentation study. The research result shows that citizen participation in Kapuas Sub-District in the process of sub-district development planning is a bit low. It also reveals that the process of the planning and decision making is unfavorable. Through quantitative approach, it can be concluded that there is a strong correlation between citizen participation and the process of sub-district development planning. Meanwhile, the hypothesis testing proves that citizen participation positively and significantly influences the process of sub-district development planning.